2021
DOI: 10.3389/fneur.2021.624696
|View full text |Cite
|
Sign up to set email alerts
|

The Delayed Neuropathological Consequences of Traumatic Brain Injury in a Community-Based Sample

Abstract: The late neuropathological effects of traumatic brain injury have yet to be fully elucidated, particularly with respect to community-based cohorts. To contribute to this critical gap in knowledge, we designed a multimodal neuropathological study, integrating traditional and quantitative approaches to detect pathologic changes in 532 consecutive brain autopsies from participants in the Adult Changes in Thought (ACT) study. Diagnostic evaluation including assessment for chronic traumatic encephalopathy (CTE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 99 publications
(138 reference statements)
3
20
0
Order By: Relevance
“…In the Sydney Brain Bank, of the 636 cases screened, only five were identified as having CTE-NC, illustrating a strikingly low prevalence (0.79%). This is consistent with a recent study reporting a low frequency of CTE-NC (0.6%) in 532 individuals from a similar community-based cohort of ageing and neurodegeneration in the USA 29 and a large-scale study reporting no CTE-NC in 310 cases from Europe. 30 There was not a single case of CTE-NC in individuals with a documented history of a TBI alone; rather, three of the cases had TBI in addition to high exposure to repetitive head impacts in collision and combat sports and two cases had no known history of neurotrauma (TBI or repetitive head impacts in sports).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the Sydney Brain Bank, of the 636 cases screened, only five were identified as having CTE-NC, illustrating a strikingly low prevalence (0.79%). This is consistent with a recent study reporting a low frequency of CTE-NC (0.6%) in 532 individuals from a similar community-based cohort of ageing and neurodegeneration in the USA 29 and a large-scale study reporting no CTE-NC in 310 cases from Europe. 30 There was not a single case of CTE-NC in individuals with a documented history of a TBI alone; rather, three of the cases had TBI in addition to high exposure to repetitive head impacts in collision and combat sports and two cases had no known history of neurotrauma (TBI or repetitive head impacts in sports).…”
Section: Discussionsupporting
confidence: 92%
“… 29 additionally quantified the levels of paired helical filament tau, ß-amyloid 1–42, α-synuclein, phosphorylated TDP-43 as well as markers of inflammation (Iba1 and glial fibrillary acidic protein) in various brain regions of a large post-mortem cohort and found no association between TBI and these measures. However, in a subset of cases with more carefully matched control samples and more detailed analysis, higher levels of hippocampal tau were found in individuals with a history of TBI with loss of consciousness, 29 which is more consistent with the findings from our study. Other post-mortem studies also report that TBI is associated with greater tau and ß-amyloid pathology and greater phosphorylation-independent TDP-43.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another larger post-mortem study of 310 older individuals found that while ARTAG was frequently found in the general aging population (incidence of 38%), there was no evidence of CTE neuropathology in any individual (46). Postupna et al reviewed 532 consecutive autopsy cases from the Adult Changes in Thought (ACT) study which consisted mostly of individuals with no TBI history and found only three cases of CTE (75). Two cases had a history of falls later in life and the third case had a history of military service.…”
Section: Specificitymentioning
confidence: 99%